Systematic Literature Review: Implementasi Pendidikan Karakter Melalui Cerita Untuk Meningkatkan Kejujuran Siswa - Zahra Harahap, Atika; Sofia, Azyka; Br Sitorus, Dini Sastra; Nazwa, Khairin; Aini Lubis, Nazwa Septi; Khoiriyah, Nurul; Nurhayati, Nurhayati (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to examine the implementation of character education through stories in improving students' honesty. The method used is a systematic literature review of various relevant literature with a main focus on the application of honesty values ​​through story media, school programs, and other character learning approaches. The results of the study indicate that stories are an effective medium in conveying moral values, including honesty, because they are narrative, contextual, and easily accepted by children. The implementation of character education through stories can be done through various methods such as honesty canteens, cultural value-based learning, the Value Clarification Technique (VCT) method, and habituation through folklore or picture books. Supporting factors such as the role of teachers, family involvement, and the school environment greatly influence the success of forming students' honest character. However, challenges are also found in the consistency of implementation and the influence of the social environment. Therefore, synergy between stakeholders is needed in optimizing character education from an early age through a creative and enjoyable approach.